2020
DOI: 10.14218/jcth.2020.00062
|View full text |Cite
|
Sign up to set email alerts
|

A Case Report of Alloimmune Hepatitis after Direct-acting Antiviral Treatment in a Liver Transplant Patient

Abstract: Direct-acting antiviral (DAA) therapy is often well-tolerated, and adverse events from DAA therapy are uncommon. We report a case of a woman who underwent orthotopic liver transplant for chronic hepatitis C infection and later developed alloimmune hepatitis shortly after starting DAA therapy for recurrent hepatitis C infection. The patient developed acute alloimmune hepatitis approximately 2 weeks after starting treatment with sofosbuvir, velpatasvir, and voxilaprevir. This case report proposes a dysregulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…We may argue that recent moderate ischemic‐reperfusion injury with EAD, kidney failure and active HCV viral replication made this steatotic graft most vulnerable, playing a role in the drug‐induced injury. Noteworthy, in 2020 Choi C et al 32 published a case report of alloimmune hepatitis after 2 weeks of therapy with SOF/VEL/VOX. The patient had undergone LT with active HCV viremia 3 months before and received an HCV antibody and HBcAb‐positive graft.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We may argue that recent moderate ischemic‐reperfusion injury with EAD, kidney failure and active HCV viral replication made this steatotic graft most vulnerable, playing a role in the drug‐induced injury. Noteworthy, in 2020 Choi C et al 32 published a case report of alloimmune hepatitis after 2 weeks of therapy with SOF/VEL/VOX. The patient had undergone LT with active HCV viremia 3 months before and received an HCV antibody and HBcAb‐positive graft.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, authors concluded relating the alloimmune hepatitis to an immune system imbalance induced by the DAA regimen in a patient who already suffered from vitiligo. This highlights that every effort should be made in order to collect more data all around the world about the use of SOF/VEL/VOX after LT 31–33 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The process of autoantigen recognition is closely controlled by regulatory mechanisms in the normal state. The failure of these systems causes the autoimmune onslaught to begin and continue [43,44] . In AIH, immunoregulatory systems have been consistently identified as being impaired.…”
Section: Pathogenesismentioning
confidence: 99%